Modulation of HIV-1-host cell pathways : from virus entry to latency - Santos, Ana Catarina Taborda Godinho dos, 1987- (2016)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2017